Pengaruh reformasi administrasi perpajakan terhadap kepatuhan wajib pajak: Studi kasus di KPP Pratama Kedaton Bandar Lampung - Hani Putri Monalika; Haninun Haninun (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: The purpose of this study is to determine the effect of tax administration reforms on the level of tax compliance. A good tax administration system is a key factor in the successful implementation of tax policies. With the improvement of tax administration, it is expected to encourage taxpayer compliance. Research methodology: The research method used is a quantitative method. The samples in this study were. The data were collected using questionnaires distributed to the sample of 65 corporate taxpayers Results: The results show that the tax administration reform has a positive effect on taxpayer compliance, which means that the tax administration reform can improve taxpayer compliance Limitations: This research was only conducted on one Primary Tax Office so that the sample was small with a total of 65 samples. Contribution: this study has implications for government policies related to tax administration reforms which are very important to facilitate taxpayers in fulfilling their obligations. Keywords: Tax Administration Reform, Tax Administration System Modernization, Modern Tax Administration System, Tax Administration System, Tax Reform, Taxpayer Compliance, Corporate Taxpayer Compliance